Mind in Nature Bridging Process Philosophy and Neoplatonism. - Teixeria, Maria-Teresa (Cambridge Scholars Publisher, 2021)
This collection of essays written by leading Whitehead scholars bridges two important philosophical movements in Western philosophy separated by many centuries: Neo-Platonism and Process Philosophy. It focuses on a variety of topics, which can be found in both theories, including creativity, temporality, holism, potentiality, causality, evolution, organism, and multiplicities. They all concur with an integral, natural worldview, showing that wholeness, complexity, and indivisibility are prevalent in Nature. All in all, it brings together Neo-Platonism and Process Philosophy through the impact.